1999
DOI: 10.1144/sjg35020145
|View full text |Cite
|
Sign up to set email alerts
|

A regional geochemical assessment of some terrane relationships in the British Caledonides

Abstract: SynopsisRegional geochemical data have been systematically collected across the British Caledonides and interpreted, using single and multi-element image analysis, to provide geochemical constraints on terrane relationships. In the Hebridean Terrane, the Lewisian rocks show the characteristics of a large ion lithophile element (LILE) depleted lower crustal complex and seem unlikely to have been the source for the bulk of the overlying Torridonian clastic rocks. The psammite-dominated Moine Supergroup and the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 64 publications
2
23
0
Order By: Relevance
“…Stone et al (1999 identified two element assemblages as being of particular value in tracking geologicallycontrolled changes in sediment composition: the basic-ultrabasic elements (Cr-Ni-Mg-VTi), and the feldspar association (Rb-Sr-K-Ba), both of which had potential as lithostratigraphical mapping surrogates. Breward et al (2011) were able to extend the element distribution patterns seen in the Southern Uplands westward into the DownLongford inlier, Ireland, utilising similar geochemical data acquired there as part of the TELLUS project.…”
Section: Lithostratigraphy and Provenancementioning
confidence: 99%
“…Stone et al (1999 identified two element assemblages as being of particular value in tracking geologicallycontrolled changes in sediment composition: the basic-ultrabasic elements (Cr-Ni-Mg-VTi), and the feldspar association (Rb-Sr-K-Ba), both of which had potential as lithostratigraphical mapping surrogates. Breward et al (2011) were able to extend the element distribution patterns seen in the Southern Uplands westward into the DownLongford inlier, Ireland, utilising similar geochemical data acquired there as part of the TELLUS project.…”
Section: Lithostratigraphy and Provenancementioning
confidence: 99%
“…The implication is that stream sediment composition reflects the Lower Palaeozoic bedrock geology and that glacial smearing effects are minimal (Stone et al 2006 and references therein). Stone et al (1999) Leeder (1973Leeder ( , 1976, citing the evidence of Smith (1967), concluded that southwesterly-directed currents predominated, thus supporting his concept of an interior basin, although this model was disputed by Paterson et al (1976) who favoured an eastward flowing river system. Despite the undoubted introduction of some 'foreign' sediment, the persistence of the CaO geochemical lineament strongly suggests that much of the material forming the Stratheden Group 'Upper Old Red Sandstone' lithologies of the Tweed Basin was derived from the local Silurian sandstones.…”
Section: The Influence Of Glaciationmentioning
confidence: 99%
“…The regional tectono-stratigraphical significance of the geochemical patterns has been discussed by Stone et al (1999 who have identified two element assemblages as being of particular value in tracking geologically-controlled changes in sediment composition: the basic-ultrabasic elements (Cr-Ni-Mg-V-Ti), and the feldspar association (Rb-Sr-K-Ba).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of previous studies have identified several element assemblages as being of value in tracking geologically-controlled changes in sediment composition across the Southern Uplands (Stone et al, 1993(Stone et al, , 1999. Of particular value under appropriate circumstances are the basic-ultrabasic element suite Cr-Ni-Mg-V, the feldspar association Rb-Sr-K-Ba, the resistate mineral association Ti-Y-Zr-La-Cr and the base metal association Cu-Pb-Zn-As.…”
Section: Variations In the Chemical Composition Of Stream Sedimentmentioning
confidence: 99%